Trends in Integrated Insect Pest Management - Soundararajan, R. P.; Narayanasamy, Chitra (IntechOpen, 2020)
The science of entomology deals with various aspects of insects. In agricultural crop production, insects play a major role in damaging crop plants as well as protecting the crops from pests through biological control strategies. The approach of integrated pest management is more relevant in the present scenario of dependency on synthetic chemicals. Techniques of biological control with entomopathogenic nematodes, the integrated approach as well as the impact of chemical insecticides are discussed in this book under various chapters. Management of storage pests with different storage structures for maize is described. Development of insecticide resistance against insects is a major reason for the failure or overuse of chemical insecticides. The reasons and mechanisms of insecticide resistance are discussed in the book. An interesting chapter on the impact of newer insecticide molecules against pollinators is also described.